2022
DOI: 10.21037/atm-22-5772
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing analysis of the role of β-catenin in F-actin reorganization in embryonic palatal mesenchymal cells

Abstract: Background: Palatogenesis is a highly regulated and coordinated developmental process that is coordinated by multiple transcription factors and signaling pathways. Our previous studies identified that defective palatal shelf reorientation due to aberrant mesenchymal β-catenin signaling is associated with Filamentous actin (F-actin) dysregulation. Herein, the underlying mechanism of mesenchymal β-catenin in regulating F-actin cytoskeleton reorganization is further investigated.Methods: Firstly, β-catenin silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Recently, Liu W et al conducted transcriptome analysis and suggested that Saa3 and Cxcl5 may be the intermediate targets for β-catenin in the regulation of F-actin rearrangement in mouse embryonic palatal mesenchymal cells. However, no differential expression of these Frontiers in Physiology frontiersin.org genes was observed in mice in vivo (Liu et al, 2022). Taken together, these findings clarify the crucial role of β-catenin-mediated actin polymerization and rearrangement in palatal development; however, the specific mechanisms need to be further explored.…”
Section: Actin Polymerization Mediates Tissue and Organ Morphogenesismentioning
confidence: 79%
“…Recently, Liu W et al conducted transcriptome analysis and suggested that Saa3 and Cxcl5 may be the intermediate targets for β-catenin in the regulation of F-actin rearrangement in mouse embryonic palatal mesenchymal cells. However, no differential expression of these Frontiers in Physiology frontiersin.org genes was observed in mice in vivo (Liu et al, 2022). Taken together, these findings clarify the crucial role of β-catenin-mediated actin polymerization and rearrangement in palatal development; however, the specific mechanisms need to be further explored.…”
Section: Actin Polymerization Mediates Tissue and Organ Morphogenesismentioning
confidence: 79%